Recovery of associated and internalized Salmonella in broiler skin by stomaching and grinding. (March 2017) - Singh, P.; Silva, M.F.; Ryser, E.T.; Ha, S.D.; Kang, I.
Abstract: The objective of this study was to evaluate the recovery of associated and internalized Salmonella by stomaching and grinding broiler skin during exposure at 4 °C and at room temperature, using a two-strain green fluorescent protein (GFP) labeled cocktail of Salmonella Enteritidis. In the first experiment, broiler skins were immediately taken from eviscerated carcasses and exposed to a Salmonella cocktail containing ∼1 × 10 9 CFU/ml for 0.5, 6, 12, 24, and 48 h at 4 °C. After each exposure, two 1-min stomachings and subsequent grinding of the stomached skin were conducted to quantify loosely associated (from two stomachings) and tightly associated (from grinding) Salmonella on the skin, respectively. Broiler skins exposed to Salmonella for 24 and 48 h were also examined by confocal microscopy before and after the two stomachings. The 1st and 2nd stomachings recovered an average of 71 and 17% of the Salmonella population, respectively, with an additional 12% of the cells recovered after subsequent grinding, regardless of incubation time. Based on the confocal images, most Salmonella were removed after two stomachings, however a few cells further penetrated from 9 to 29 μm into the skin. In the second experiment, broiler skins were immersed in the same two-strain Salmonella cocktail (∼1 × 10 8 cells/ml) and dip-inoculated for 2 min with/without stomaching at room temperature. Based on the confocal images, Salmonella penetrated the flat skin surfaces and crevices up to 10 and 68 μm without stomaching, respectively, and up to 62 and 132 μm with stomaching. The presence of free-floating Salmonella cells in the skin crevices indicates that entrapped water is important for bacterial translocation in poultry skin. These findings indicated that extent of observable Salmonella association, penetration, and subsequent recovery from poultry skin is related to both surface topography of poultry skin and method of sample processing. Highlights: GFP-tagged Salmonella cells were used for recovery in broiler skin. Stomaching and grinding recovered 88 and 12% of the cells, respectively. After stomaching, a few remaining Salmonella further penetrated the broiler skin. Salmonella association and penetration were related to surface topography of poultry skin.